Changing regional weather-crop yield relationships across Europe between 1901 and 2012 - Trnka, M.; Olesen, J. E.; Kersebaum, K. C.; Roetter, R. P.; Brazdil, R.; Eitzinger, J.; Jansen, S.; Skjelvag, A. O.; Peltonen-Sainio, P.; Hlavinka, P.; Balek, J.; Eckersten, H.; et al. (Inter-Research, 2016)
Europe is, after Asia, the second largest producer of wheat in the world, and provides the largest share of barley. Wheat (and to a similar extent, barley) production in Europe increased by more than 6-fold during the 20th century. During the first half of the 20th century, this was driven by expanding the harvested area. This was followed, from the mid-20th century, by a massive increase in productivity that in many regions has stalled since 2000. However, it remains unclear what role climatic factors have played in these changes. Understanding the net impact of climatic trends over the past century would also aid in our understanding of the potential impact of future climate changes and in assessments of the potential for adaptation across Europe. In this study, we compiled information from several sources on winter wheat and spring barley yields and climatological data from 12 countries/regions covering the period from 1901-2012. The studied area includes the majority of climatic regions in which wheat and barley are grown (from central Italy to Finland). We hypothesized that changes in climatic conditions have led to measurable shifts in climate-yield relationships over the past 112 yr, and that presently grown wheat and barley show a more pronounced response to adverse weather conditions compared to crops from the early 20th century. The results confirm that climate-yield relationships have changed significantly over the period studied, and that in some regions, different predictors have had a greater effect on yields in recent times (between 1991 and 2012) than in previous decades. It is likely that changes in the climate-yield relationship at the local level might be more pronounced than those across the relatively large regions used in this study, as the latter represents aggregations of yields from various agroclimatic and pedoclimatic conditions that may show opposing trends.
Keywords: climatic trend; weather-crop yield relationship; wheat; barley; yield trend; drought; Europe; winter-wheat yields; climate change; variability; sensitivity; shifts; trends; Denmark